UJI KANDUNGAN FLAVONOID DAN TANIN PADA EKSTRAK DAUN DAN KULIT POHON KAYU MAHONI (Swietenia mahagoni) - Syaiful Anam; A. Sri Hartanti; Miftachul Chusnah; Yessita Puspaningrum (Universitas Tribhuwana Tunggadewi, 2023)
The mahogany tree has many benefits, one of which is the leaves and bark of the mahogany tree. This study aims to determine the content of flavonoids and tannins in the leaves and bark of mahogany trees. The results of phytochemical tests on leaves and bark of mahogany trees showed high values. Extraction was carried out by maceration method and for phytochemical tests using spectrophotometry. Mahogany bark flavonoid content with an absorbance of 0.039 with a concentration of 100 ppm has a value of 6.6% QE(quercetin equivalent) while the highest content is found in mahogany bark, namely, the absorbance of 1.25 with a concentration of 400 ppm has a value of 6.34% TAE (tannic acid equivalent).